Determinants of Preference of Milk and Milk Products : The Case of Rural and Urban Areas in Kanchipuram District of Tamil Nadu - Rameshkumar, S.; Vikraman, A. (Indian Journal of Marketing, 2018)
This paper attempted to examine the factors that influenced the decision of rural as well as urban consumers of Kanchipuram District of Tamil Nadu in the purchase of milk and milk products and thus tried to bring to fore the similarities, if any, in such decisions. The primary data collected from a sample size of 360 respondents selected through the convenient sampling technique were put to a microscopic analysis by employing the percentage analysis, chi-square test, and factor analysis approach. The results showed that among the various factors, the product - oriented factor, which included the variables like high quality, affordable price, taste, aroma, thickness, availability in required quantity, and no harmful effects had a greater influence in determining the preference of the respondents towards milk and milk products. However, no significant difference in the factors influencing the purchase decision of milk by the consumers of both the areas was traceable and a significant difference was found in the factors influencing their purchase decision of milk products. As the milk consumers in the study area were very much concerned about the product oriented factors at the time of purchase of milk and milk products, utmost care and attention of the milk producers and distributors on these factors would certainly ensure maximization of profitability by exploiting the potential still untapped in this industry.